Thermal Efficiency of Power Module “Boiler with Solar Collectors as Additional Heat Source” For Combined Heat Supply System - Denysova A.E.; Mazurenko A.S.; Denysova A.S. (Problems of the Regional Energetics)
The purpose of work is to increase the efficiency of the combined heat supply system with solar collectors as additional thermal generators. In order to optimize the parameters of combined heat supply system the mathematical modeling of thermal processes in multi module solar collectors as additional thermal generators for preheating of the water for boiler have been done. The method of calculation of multi-module solar collectors working with forced circulation for various configurations of hydraulic connection of solar collector modules as the new result of our work have been proposed. The results of numerical simulation of thermal efficiency of solar heat source for boiler of combined heat supply system with the account of design features of the circuit; regime parameters of thermal generators that allow establishing rational conditions of its functioning have been worked out. The conditions of functioning that provide required temperature of heat carrier incoming to boiler and value of flow rate at which the slippage of heat carrier is not possible for different hydraulic circuits of solar modules have been established.